Internationalization of Higher Education in Vietnam Opportunities and Challenges - Tuyết, Trần Thị (VNU Journal of Foreign Studies; Vol 30 No 3, 2014)
Abstract: In the contemporary global academic environment, internationalization of higher education has become a common trend in both developed and developing countries. InVietnam, a developing country inAsia, initiatives such as branch campus, transnational collaborative arrangements, sandwich programs, English-medium programs and degrees have been put in place as part of higher education internationalization. This has created both opportunities and challenges for the development of the Vietnamese higher education system. On the one hand, it creates the opportunity for local universities to cooperate with foreign partners, to provide international and cross-cultural perspectives for their students, and to enhance their curricula. Thus it may help the local institutions improve the quality and cultural composition of their student cohort, gain prestige and earn more income. However, these initiatives and programs are largely coming from and controlled by the industrialized North, with the key motives of earning money and expanding power. Therefore, it requires that the local government and institutions have strong capability to monitor international initiatives, to be selective in their cooperation and in the lessons they should learn in order to improve the teaching and learning quality for the Vietnamese higher education system. Keywords: Higher education, internationalization, Vietnam, challenges, opportunities.